2010
DOI: 10.1007/s00383-010-2817-9
|View full text |Cite
|
Sign up to set email alerts
|

A rare presentation of crush injury: transanal small bowel evisceration. Case report and review of the literature

Abstract: Evisceration of the small intestine through the anus is an extremely rare event in children. We report a 2-year-old boy who sustained transanal small bowel evisceration associated with bilateral diaphragmatic rupture, left diaphragmatic herniation, and spinal cord injury without radiographic abnormality which happened after crushing by motor vehicle. We reviewed children with transanal small bowel evisceration and discussed etiological differences between children and adult. We also discussed the basic princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…Seuls 20 cas pédiatriques ont été rapportés dans la littérature [1]. Ce phénomène est plus connu chez l'adulte où des formes spontanées ont été décrites, occasionnées par les facteurs d'hyperpression intra-abdominale comme les exonérations, la toux et les vomissements [2].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Seuls 20 cas pédiatriques ont été rapportés dans la littérature [1]. Ce phénomène est plus connu chez l'adulte où des formes spontanées ont été décrites, occasionnées par les facteurs d'hyperpression intra-abdominale comme les exonérations, la toux et les vomissements [2].…”
Section: Discussionunclassified
“…Les lésions associées (intra et/ou extra-abdominales) sont souvent sévères et peuvent rendre le tableau clinique plus dramatique [1,711]. …”
Section: Discussionunclassified
See 1 more Smart Citation
“…The gap usually sits on the anterior surface of the rectum near the peritoneal reflection [3] and may be transverse [12] or longitudinal [13]. Petras et al [14] demonstrated clearly an aetiopathogenic link between focal rectal ischemia and perforation.…”
Section: Pathogenic Aspectsmentioning
confidence: 99%
“…The definitive repair of rectal prolapse by rectopexy or by intervention of Altemeier can be considered in eligible candidates [1]. Trans-anal evisceration of the small intestine shows high mortality [13]. The review of literature by Morris et al [17] revealed 53 cases of evisceration of the small bowel on rectal prolapse since the first case described by Brodie and of these 53 cases, 22 (41.5%) cases had died.…”
Section: Therapeutic Aspects and Prognosismentioning
confidence: 99%